THE EFFECT OF INFORMATION TECHNOLOGY AND THE QUALITY OF HUMAN RESOURCES ON ACCOUNTING INFORMATION SYSTEMS - Tuswoyo, Tuswoyo; Hartanti, Dessi Dwi (International Peneliti Ekonomi, Sosial dan Teknologi, 2020)
This study is to analyze the amount of the effect of the implementation of information technology and the quality of human resources simultaneously affecting the effectiveness of the accounting information system in the Transportation Service of DKI Jakarta Province. The research approach used is quantitative research methods. The type of research approach according to the level of explanation is included in associative/ relationship research. The variables used in this study are the implementation of information technology as the X1 variable, the quality of human resources as the X2 variable and the effectiveness of the accounting information system as the Y variable. The population taken in this study is the number of employees of the DKI Jakarta Provincial Transportation Service consisting of 273 people with a total sample of 73 people. Based on the results of the research and discussion by the author, it can be concluded that: 1). There was a partial influence between the implementation of information technology on the effectiveness of the accounting information system; 2). There was a partial influence between the quality of human resources on the effectiveness of the accounting information system; 3). Based on the results of the multiple X1 and X2 correlation analysis to Y, the value of R Square obtained was 0.863. The simultaneous implementation of information technology and the quality of human resources to the effectiveness of the accounting information system contributed 86.3%. From the results of multiple regression analysis, the equation was: ? = a + b1X1 + b2X2 = -4,270 + 0,173X1 + 0,935X2 To test the significance of the implementation of information technology and the quality of human resources simultaneously on the effectiveness of the accounting information system, the Ftest test was conducted. From the calculation of the value of t table, it was known that the value of Ftable = 3,134 whose value was smaller than the value of Fcount, which was = 211,037. The conclusion was Fcount > Ftable or 211,037 > 3,134, then value was significant